2009
DOI: 10.1159/000223073
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Determining Loci and Sex Chromosomes in the Family Salmonidae

Abstract: Salmonids are descended from a common ancestor that underwent an autotetraploidization event. After a whole genome duplication species could deal with sex determination by deleting one copy of SEX, the sex determining locus, or by recruiting a duplicated transcription factor to become a novel sex determining gene. It is not known which if any of these strategies salmonids adopted, but it appears that they all have primarily a genetic mechanism of sex determination with male heterogamety. The sharing of sex-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 172 publications
2
90
0
2
Order By: Relevance
“…Interestingly, the Y chromosomes in the investigated salmonid species are not syntenic, and hence the SD locus is located on different chromosomes. Before the discovery of sdY, the idea of a (likely small) conserved but mobile SD locus had been put forward for the salmonid family as a possible explanation for the fact that different chromosomes showed sex linkage in different species (Davidson et al 2009) and even within species (Moghadam et al 2007;Küttner et al 2011;Eisbrenner et al 2013).…”
Section: Suggested Mechanisms For the Emergence Of New Master Sex Detmentioning
confidence: 99%
“…Interestingly, the Y chromosomes in the investigated salmonid species are not syntenic, and hence the SD locus is located on different chromosomes. Before the discovery of sdY, the idea of a (likely small) conserved but mobile SD locus had been put forward for the salmonid family as a possible explanation for the fact that different chromosomes showed sex linkage in different species (Davidson et al 2009) and even within species (Moghadam et al 2007;Küttner et al 2011;Eisbrenner et al 2013).…”
Section: Suggested Mechanisms For the Emergence Of New Master Sex Detmentioning
confidence: 99%
“…Gonad differentiation begins early in development in Atlantic salmon, as many of the major genes involved in sex determination and differentiation are upregulated in the embryonic stage (von Schalburg et al, 2011). Gonad development is plastic throughout early development, and exposure to aqueous and dietary EDCs can skew sex ratios (Davidson et al, 2009;Norrgren et al, 1999) by binding to the estrogen receptor(s) (Kloas et al, 2000;Scholz et al, 2013). Exposure to estrogenic compounds in the wild during early development could have profound effects on population dynamics and recruitment success of Atlantic salmon by affecting sex ratios and reproductive development.…”
Section: ␣-Ethinylestradiolmentioning
confidence: 99%
“…An alternative strategy is to recruit a novel sex-determining master gene from among the duplicated genes encoding transcription factors. Either strategy could potentially lead to a species radiation [Davidson et al, 2009].…”
mentioning
confidence: 99%
“…The construction of genetic maps that include the sex-determining locus, SEX (defined as the male phenotype), for several salmonid species revealed that there is a lack of conservation of synteny of SEX and microsatellite markers in Atlantic salmon (Salmo salar) , brown trout (Salmo trutta) , Arctic charr (Salvelinus alpinus) , coho salmon (Oncorhynchus kisutsch) , chinook salmon (Oncorhynchus tshawytscha) and rainbow trout (Oncorhynchus mykiss) [Woram et al, 2003;Davidson et al, 2009]. These genetic maps place SEX at the end of a linkage group in these salmonids, and on this basis it has been assumed that SEX is located close to the telomeric regions in their respective chromosomes.…”
mentioning
confidence: 99%